STRENGTH, TIMING, SETTING AND CAUSE OF MID-PALAEOZOIC EXTINCTIONS - House M.R. (My University, 2002)
Much has been written over the last 20 yr on the Upper Kellwasser Event (Frasnian/Famennian or F/F boundary) as the major extinction event of the Middle Palaeozoic (Devonian) and as the fifth largest extinction event in the Phanerozoic; this opinion was based on analysis of family range data. These views are misleading. A current analysis of family extinction data, largely based on The Fossil Record 2, but updated in some respects, supersedes the data base of Raup and Sepkoski (1982) and shows that the Famennian has the highest total family extinction of marine taxa, with the Givetian in second and Frasnian in third place. If these new data are related to current (unreliable) estimated length of stages, then the severest extinction rates are: first, the Givetian at 14.2 family extinctions per Ma, secondly the Frasnian at 11.2 and thirdly the Eifelian at 6.8. Many short-term ‘events’ have been named for the Devonian based on short-term distinctive sedimentary and/or faunal perturbations. A review of these shows how they are often transgression/regression couplets, many with an association of anoxia and poor in benthos, or spreads of pelagic faunas, and some are phased and complex. Evidence is presented to suggest that the transgressive pulses correspond to warm temperatures which are terminated by cooling. Possible links with orbitally forced patterns are considered. A common explanation seems required, not just for the Kellwasser Event, but for all these events. The relation of the family stage extinctions, especially the Kačák, Taghanic, Kellwasser and Hangenberg Events, which are of much more limited duration, is discussed particularly in relation to new and more precise data of the extinction events known within these stages. In the absence of detailed studies for many groups, those that have been well documented may serve as a temporary proxy for others.